İDEOLOJİK KİMLİKLERİNE GÖRE KÜRTLERİN FARKLILAŞAN ALGILARI- DİYARBAKIR ÖRNEĞİ - Osman ALACAHAN (Fırat University, 2021)
This research tries to comprehend differences among Kurdish ethnicity in terms of ideological/political identity. In this study, it is found that the Kurdish Society is